Globalizing opposition to pro-environmental institutions: The growth of counter climate change organizations around the world, 1990 to 2018. - Jared Furuta; Patricia Bromley (PLoS ONE)
More than two decades of social scientific research has identified the growing network of corporations, think tanks, nonprofits, and advocacy organizations that aim to obstruct climate change action within the United States. Conventional arguments emphasize the role of economic self-interest (e.g., wealthy and powerful corporations) in shaping the rise of an organized "counter climate change movement" that seeks to discredit evidence about anthropogenic climate change and derail solutions to address the problem. In this paper, we track the growth of counter climate change organizations around the world and emphasize the role of reactionary cultural dynamics in driving their emergence. As climate change discourse is infused in more areas throughout society, climate change issues become more salient in the public sphere, generating adversarial grievances, identities, and mobilization among oppositional groups. Drawing on panel logistic regression models for 162-164 countries from 1990 to 2018, we find that counter climate change organizations are most likely to develop in countries with more extensive state policies and structures oriented toward protecting the natural environment, net of a variety of factors that account for a country's economic interests or its overall capacity to produce domestic associations.